Recent advances in ferroptosis and therapeutic strategies for glioblastoma - Lu, Qixiong; Lu, Xiaoyang; Zhang, Yuansheng; Huang, Wei; Zhou, Hu; Li, Tao (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is an emerging form of cell death characterized by the over-accumulation of iron-dependent lipid peroxidation. Ferroptosis directly or indirectly disturbs glutathione peroxidases cycle through diverse pathways, impacting the cellular antioxidant capacities, aggravating accumulation of reactive oxygen species in lipid, and it finally causes oxidative overload and cell death. Ferroptosis plays a significant role in the pathophysiological processes of many diseases. Glioblastoma is one of the most common primary malignant brain tumors in the central nervous system in adults. Although there are many treatment plans for it, such as surgical resection, radiotherapy, and chemotherapy, they are currently ineffective and the recurrent rate is almost up to 100%. The therapies abovementioned have a strong relationship with ferroptosis at the cellular and molecular level according to the results reported by numerous researchers. The regulation of ferroptosis can significantly determine the outcome of the cells of glioblastoma. Thus ferroptosis, as a regulated form of programed cell death, has the possibility for treating glioblastoma.